Lingüística da cautela e da expresividade: sinónimos galegos de ‘demo’, ‘morrer’ (‘morte’), ‘porco’, ‘sacerdote’ e ‘sapo’ - Alonso Montero, Xesús (Madrygal. Revista de Estudios Gallegos, 2008)
In this article we are shown the results of a linguistic survey about how the speaker uses expressive, humoristic and recreational terms in a range of semantic universes.